Kuat Tekan Mortar dengan Berbagai Campuran Penyusun dan Umur - Adi, Rudi Yuniarto (Department of Civil Engineering, Diponegoro University, 2009)
In the implementation of construction, during this type of mortar of the new indicator is based on water-resistant and not waterproof. However, besides the function to actually hold water, mortar functions also have a burden. Often required in the implementation of that day in the walls of a maximum of 1 meter regardless of the composition of the mortar mix used. This is because the lack of discussion of the strength of mortar. The results of this study conclude that a strong press and mortar akan increased sharply since the age of 0 to 12 days, and a strong improvement over the press and mortar at the age of 13 days to 90 daysKeywords: Mortar, composition, mixture, strong, press, agePermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3420[How to cite: Adi, R.Y. (2009). Kuat Tekan Mortar denganÂ Berbagai Campuran Penyusun dan Umur, Jurnal Media Komunikasi Teknik Sipil, 17 (1): 67-84]